To find the answer you would need to add 11 to 75 and then that is 86 so then divide that by 1 and the answer is 86
Answer:
b=7
Step-by-step explanation:
A=bh/2
28=8b/2
56=8b
b=7
Step-by-step explanation:
<u>Given functions:</u>
<u>Find (f*g)(6):</u>
- (f*g)(6) = f(6)*g(6) = 6(6 - 1)*3(6) = 30*18 = 540
<u>In case it is a composite function (f · g)(6) the answer is different:</u>
- (f · g)(6) = f(g(6)) = f(3*6) = f(18) = 18*(18 - 1) = 306
Answer:
<h2>16/18</h2>
Step-by-step explanation:
<h2>hopes this helps. Mark as brainlest plz!</h2>